Eksplorasi Persepsi Siswa Terhadap Pemanfaatan Edu-Games Digital dalam Pembelajaran Bahasa Inggris: Studi Kualitatif di Sekolah Menengah - Rajagukguk, Rosdiana (LPPM Institut Pendidikan Nusantara Global, 2025)
The digital transformation in education has encouraged the adoption of innovative learning media, one of which is the use of educational games (edugames) in English language teaching. This study aims to explore secondary school students' perceptions of the use of digital edugames in English language learning. A qualitative approach with a case study design was employed to gain an in-depth understanding of students' learning experiences through in-depth interviews, participant observation, and documentation. Participants included eighth and ninth grade students from a secondary school in North Sumatra who actively used edugame applications such as Quizizz, Wordwall, and Kahoot during their learning activities.The findings reveal that students hold positive perceptions of edugames in terms of motivation, learning engagement, and content comprehension. Digital games were found to support vocabulary and grammar acquisition in a contextual and enjoyable environment. However, technical constraints such as device availability and internet access remain challenges in implementation. Students’ perceptions were also shaped by the role of teachers in designing and facilitating the use of edugames in a structured and pedagogically sound manner. Hence, digital edugames are considered effective when integrated systematically and interactively into instructional planning. This study highlights the importance of technology-integrated learning approaches and students' active involvement in selecting instructional media.